Steam Properties Prediction in Steam Pipeline System using Microsoft EXCEL VBA - Saad, Muhammad Syauqie (2022)
Steam is widely used in the power generation industry. The pipeline system is used to transport the steam from a boiler to the steam turbine. However, steam pipeline is a complex system that is time-consuming in the developing process.